1998
DOI: 10.1021/jp982309z
|View full text |Cite
|
Sign up to set email alerts
|

Time-Resolved Spectral Investigation of Bacteriochlorophyllaand Its Transmetalated Derivatives [Zn]-Bacteriochlorophyllaand [Pd]-Bacteriochlorophylla

Abstract: The lowest excited singlet (S1) and triplet (T1) states of bacteriochlorophyll a (BChl) and its central metal derivatives [Zn]- and [Pd]- BChl were investigated by femtosecond time-resolved absorption and fluorescence spectroscopy. In contrast to previously reported dynamic solvation effects on the picosecond time scale for BChl, no short kinetic components were observed for BChl and [Zn]-BChl provided that photochemical transformations of the pigments caused by multiple excitation are avoided. The S1 lifetime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
64
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(71 citation statements)
references
References 53 publications
7
64
0
Order By: Relevance
“…The Q y fluorescence decays mono-exponentially, and then the decay time was determined to be 3.6±0.05 ns. The determined Q y lifetime in this study agrees with the reported value [13,16,30]. The results are summarized in Tab.…”
Section: Contributed Articlesupporting
confidence: 90%
See 2 more Smart Citations
“…The Q y fluorescence decays mono-exponentially, and then the decay time was determined to be 3.6±0.05 ns. The determined Q y lifetime in this study agrees with the reported value [13,16,30]. The results are summarized in Tab.…”
Section: Contributed Articlesupporting
confidence: 90%
“…Positive absorbance change was also observed immediately after excitation. These broad absorbance change has been previously assigned to the transient absorption from Q y to a higher-lying excited state (hereafter we will refer to this transient absorption as the Q y transient absorption) [13,14]. A comparison of the photo-induced absorption spectra taken at 0.1 ps shows the marked difference between excitation to the Q x band at 2.17 eV and to the Q y band at 1.59 eV, whereas the photoinduced absorption spectra taken at 1.0 and 10 ps show the similar spectral feature both after excitation to the Q x and Q y bands.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…The first EADS is associated with the effective lifetime (s eff ) of the B800. Since, B800s are monomeric BChl molecules with an intrinsic lifetime (s int ) of *2.9 ns at RT (Connolly et al 1982;Musewald et al 1998;Niedzwiedzki and Blankenship 2010) it is apparent that ultrafast energy transfer to the B850 exciton state occurs. Simple calculation of B800 state decay rates (1/s eff = 1/s int ?…”
Section: Resultsmentioning
confidence: 99%
“…This effect is especially important in the case of palladium or platinum complexes, which are used as very effective luminescence markers [5][6][7][8]. Recently, a palladium(II) bacteriochlorophyll complex has been proposed as a PDT sensitizer [9]. Moreover, palladium(II) porphyrins may become important as protein cross-linking mediators [10].…”
Section: Introductionmentioning
confidence: 99%